Prevalência da síndrome metabólica em receptores de transplante renal de acordo com o gênero e tempo pós-transplante - Garcia, Cristiane Lopes (2014)
Metabolic syndrome (MS) is defined as a set of cardiovascular risk factors including obesity, systemic high blood pressure (SHBP), changes in glucose metabolism and dyslipidemia. The prevalence of MS in renal transplant recipients (RTR) ranges from 15% to 65%, increasing the risk of cardiovascular disease (CVD) and reducing renal allograft survival in the long term. The objectives of this study were to determine the prevalence and frequency of MS in renal transplant patients according to gender and time of transplantation and to evaluate renal function in patients with and without MS. Patients and Methods: Crosssectional study conducted from August 2012 to September 2013 involving 153 renal transplant recipients. MS was defined according to the National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATP III). The sample was divided into two groups: patients with metabolic syndrome (WMS patients) and patients without metabolic syndrome (WoMS patients) and according to gender. The WMS patients were stratified into quartiles according to the renal transplantation period (RTP), and variables related to MS were analyzed for both sexes. Results: MS was diagnosed in 58.1% of the studied population, specifically in MS was found 58.4% of men and 41.6% of women (P ˂ 0.05). The male and female with MS were 48.8 ± 11.6 years old vs. 47.1 ± 12.7 years old and the time of post transplantation was 76.1 ± 76.5 months vs. 84.7 ± 65.4 months, respectively (P >0,05). When we compared the sexes in the WMS group, systolic blood pressure (SBP) was higher in men (137.0 ± 18.1 vs. 128.9 ± 13.6 mmHg, P= 0.029), while the other components of MS did not exhibit significant differences. With respect to renal function, when we compared the sexes in the WMS group, the serum creatinine (sCr) was higher in men (1.73 ± 0.69 vs. 1.31 ± 0.47 mg/dL, P= 0.0012), while the urinary protein/creatinine ratio was higher in women (0.48 ± 0.69 vs. 0.37 ± 0.48 mg/dL, P=0.0150). We found no significant difference in the estimated glomerular filtration rate (eGFR) between WMS and WoMS patients for women and men (50.6 ± 19.1 vs. 50.1 ± 18.3 mL/min/1.73 m², P=0.909). We found a significant positive association between eGFR and HDL-c levels (r=0.3371; P=0.0145) for WMS men. The MS components showed no significant differences in RTP for different interquartile ranges, except for diastolic blood pressure (DBP) in women, where there was a significant variation among the quartiles evaluated (P=0.0009). Conclusion: the prevalence of MS was similar in the different quartiles in both sexes, in relation to time post TX. There was no significant difference in eGFR in patients WMS and WoMS, in both sexes. Concluding that the MS did not vary in relation to time post transplant.